Functional significance of senescence and autophagy in cancer-associated fibroblasts from oral squamous cell carcinoma / Tan May Leng - Tan, May Leng (2020)
Oral squamous cell carcinoma (OSCC) is a malignancy that arises from the epithelial cells within the oral cavity. It accounts for approximately 355,000 new cases worldwide and is exceptionally prevalent in particular geographical areas such as Papua New Guinea, the Indian subcontinent and South-East Asian countries. Despite advances in surgical management and therapeutic approaches, the five-year survival rate of OSCC patients has not improved significantly over the past few decades. The mortality associated with OSCC is particularly high often due to late presentation, locoregional recurrence, distant metastases and the development of second primary tumours. A comprehensive understanding of the molecular pathogenesis of OSCC is required to identify new druggable targets and inform innovations in the therapeutic approach. OSCCs are a heterogeneous group of tumours and, whilst the majority of tumours are aggressive and genetically unstable (GU-OSCC), a subset of genetically stable cancers (GS-OSCC) has been identified that have a more favourable prognosis. Intriguingly, cancer-associated fibroblasts (CAFs) from these tumours are phenotypically and functionally distinct. Many of the characteristics ascribed to CAFs are shared by autophagic and senescent fibroblasts, suggesting that these stress responses contribute to the tumour-promoting properties of CAFs. The present study was designed to investigate the possible link between autophagy and senescence in CAFs from OSCCs and normal oral fibroblasts as well as to investigate the functional significance of these CAF phenotypes in terms of promoting tumour growth, migration and invasion. The results showed that autophagic and senescent phenotypes were closely related and CAFs from GU-OSCCs were shown to be more senescent and also displayed impaired autophagic flux than normal oral fibroblasts and CAFs from GS-OSCCs. Next, the contribution of autophagy to the activated and senescent phenotypes of oral fibroblasts was investigated using TGF-β1 as an inducer of myofibroblast differentiation and iv senescence, together with inhibitors of autophagy. The results demonstrated that altered autophagy could regulate the activated and senescent phenotypes in oral fibroblasts. This had functional significance because conditioned media collected from oral fibroblasts with altered autophagy significantly enhanced migration and invasion of OSCC cells in vitro. These data indicate that the autophagy-regulated secretion by fibroblasts might be responsible, at least in part, for modulating the malignant phenotypes of OSCC cells. Lastly, an in vitro model to conditionally induce senescence in normal oral fibroblasts was established. Using this model that allowed synchronous induction of senescence in normal fibroblasts, it was demonstrated that the secretome from senescent fibroblasts enhanced OSCC cell migration and invasion. Taken together, the results of the present study suggest that the physiological states of CAFs within the OSCC tumour microenvironment might reflect different stages of the same sequential pathway and/or be part of a unified biological programme in which autophagy precedes activation and subsequent senescence during the acquisition of pro-tumorigenic CAF phenotypes. These physiological stages of oral CAF transdifferentiation could possibly be targeted therapeutically in the future for the better clinical management of patients with OSCC.